Oral rehydration program and reduction of mortality from acute diarrheal disease. Cali, 1982-1986 (Colombia Medica, 1989)
An assessment of the Diarrhoeal Disease Programme developed in Cali, Colombia, among children below five years, from 1982 to 1986 was performed, considering process, results, and impact measurements. The above period was compared with the earlier one, i.e., 1977-1981. In the beginning, all the activities required for the implementation of the program were carried out, such as education of health workers and members of the community, diffusion of the program's contents, and mainly community participation through the so-called Unidades de Rehidratación Oral Comunitaria. Most of the activities were maintained during the five years evaluated. Mortality rates due to diarrhoea showed a steady decrease by more than 50%, as well as case fatality ratio and hospital discharges. Morbidity increased, perhaps due to improvements in earlier detection and better covering by the community mothers linked to the program. A linear regression model for mortality was performed to reach clearer conclusions about trends during the examined periods and estimate avoidable deaths.